Failure Mode and Effect Analysis for Intercity Train Wheel System - Mohd Zaid, Muhammad Iqmal Syahmi; Selimin, Mohamad Ali; Abdul Hamid, Nor Aziati; Baharin, Nuramira Najihah; Jumiran, Amirul Afif (Research in Management of Technology and Business, 2024)
Beyond ensuring passenger safety, a key priority is maintaining the train's components in optimal condition to ensure smooth operations. This effort aims to deliver a seamless and worry-free experience for all, minimizing the risk of accidents or delays due to faulty parts. This study investigates the maintenance strategies for rolling stock bogie wheelsets, with a focus on optimizing practices to enhance reliability and safety. Various maintenance approaches including part-specific, mileage-based, preventive, and corrective programs were analyzed to understand their impact on maintenance decision-making for bogie wheelsets. The study specifically examines the Keretapi Tanah Melayu Berhad (KTMB) maintenance operational to address bogie wheel faults, utilizing data from KTMB’s Operation and Maintenance (O&M) manuals, monthly reports, and relevant literature. The primary goal is to develop a comprehensive framework for bogie system maintenance, particularly for wheelsets, while evaluating the safety protocols necessary for effective upkeep. A significant challenge addressed in this study is the sequencing of the bogie wheelset maintenance process, achieved through detailed analysis of maintenance documents. The findings from KTMB ETS O&M manuals and literature reviews were employed to conduct a wear and tear analysis, providing insights into the operational environment. This is done mainly to improve the performance, reliability, and durability of KTMB ETS Class 91 rolling stock by proposing a robust maintenance policy. The suggested approach aligns maintenance practices with organizational objectives, enhancing operational efficiency and cost-effectiveness within the railway sector.